Stachybotrys chartarum: A Novel Biological Agent for The Extracellular Synthesis of Silver Nanoparticles and Their Antimicrobial Activity - Abdel Ghany Tarek Mohamed (Universitas Gadjah Mada, 2013)
Microbial assisted biosynthesis of nanoparticles is a rapidly progressing area of nanobiotechnology. Inthis paper Stachybotrys chartarum assisted extracellular synthesis of silver nanoparticles (AgNPs) is reportedwhen challenged with 1mM silver nitrate (AgNO3). The characterization of AgNPs was carried out visualobservation and UV-Vis spectrophotometry. Further analysis carried out by Fourier Transform InfraredSpectroscopy (FTIR), provides evidence for the presence of proteins as capping agent, which helps in increasingthe stability of the synthesized AgNPs. Transmission Electron Microscopy (TEM) investigations confi rmedthat AgNPs were formed. The synthesized silver nanoparticles were found in the range of 65-108 nm. Finally,the antimicrobial susceptibility of AgNPs synthesized was investigated which exhibited more potent activityagainst bacteria than fungi compared with using silver nitrate at concentration 1mM. Keywords: Antimicrobial activity, Stachybotrys chartarum, Silver nanoparticles